The Four Rs of Fertilizer Management - George Hochmuth; Rao Mylavarapu; Ed Hanlon (EDIS)
Supplying needed nutrients for crop production involves attention to four major fertilization factors (the 4Rs): right rate, right source, right placement, and right timing. Attention to these factors will provide adequate nutrition for crop production while minimizing the risk of loss of nutrients to the environment. In this publication each factor is described, as well as how the information can be provided from a soil test report. While not a formal part of the 4Rs, the importance of irrigation to overall nutrient management is stressed in this 4-page fact sheet written by George Hochmuth, Rao Mylavarapu, and Ed Hanlon, and published by the UF Department of Soil and Water Science, October 2014.